2017
DOI: 10.1080/02680513.2017.1316187
|View full text |Cite
|
Sign up to set email alerts
|

The silence about oral presentation skills in distance and online education: new perspectives from an Australian university preparatory programme

Abstract: Oral presentation skills are considered essential workplace skills and are therefore highly valued in higher education. However, research into this aspect of adult learning is limited, especially in the context of distance and online education. This paper reports on an innovative approach used in a university preparatory program in Australia. Distance students were responsible for choosing a topic, setting and audience, and assessment was based on their self-reflections on the experience. Such an approach repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Findings of the present study showed that speaking instructors at the sample institutions in the present study mainly used oral presentations, gave problem-solving questions, used online debates, student-created podcasts posted in a Speaking Center on Twitter, used Vocaroo to record students' presentations and Kahoot for contests and games. These kinds of speaking activities are different from those used in prior studies by Volle (2005) , Murugaiah (2016) , Castillo (2016) , McDougall and Holden (2017) , Galindo et al (2020) , and Martin (2020) which used audio emails, Internet-based oral conversations with the instructor using MSN Messenger, computer-assisted pronunciation instruction, Pecha Kucha (PK) presentations, i.e., slides containing visuals with minimal text and presented in twenty seconds, Second Life, portfolio reflections, student-created videos and use of Internet-based material.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Findings of the present study showed that speaking instructors at the sample institutions in the present study mainly used oral presentations, gave problem-solving questions, used online debates, student-created podcasts posted in a Speaking Center on Twitter, used Vocaroo to record students' presentations and Kahoot for contests and games. These kinds of speaking activities are different from those used in prior studies by Volle (2005) , Murugaiah (2016) , Castillo (2016) , McDougall and Holden (2017) , Galindo et al (2020) , and Martin (2020) which used audio emails, Internet-based oral conversations with the instructor using MSN Messenger, computer-assisted pronunciation instruction, Pecha Kucha (PK) presentations, i.e., slides containing visuals with minimal text and presented in twenty seconds, Second Life, portfolio reflections, student-created videos and use of Internet-based material.…”
Section: Discussionmentioning
confidence: 65%
“…In Australia, distance students enrolled in a university preparatory program chose a topic, set an audience, gave an oral presentation, and reflected on their experience. The students' responses via portfolio reflections and interviews indicated that this activity fulfilled their needs and that oral presentations were a meaningful and transformative experience McDougall and Holden (2017) .…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, she adopted this approach because Androgogy per se lacked the socioemotional variables identified in other theories of learning which she believed was critical to her analysis. Her previous work (McDougall & Holden, 2017) investigated oral presentation skills in distance and online education. That study adopted Androgogy as its theoretical lens and it is interesting to note how her current thinking is pushing the boundaries of her previous theoretical frame in order to understand more fully adult learning.…”
Section: Moving Forward With Both Theory and Practicementioning
confidence: 99%
“…Castillo (2016) states that as long as the adult learners are well-acquainted with web-based technologies and digital platforms and skills, they would benefit from the listening and speaking tasks conducted online. McDougall and Holden (2017) observed the positive attitude of tertiary level students about online speaking programs if the guidelines such as the topic, audience were set clear that would make the oral presentations fulfilling and meaningful. Galindo, Gregori and Martinez (2020) emphasized the role of making the assessment criteria clear so that the students would perform better in their second drafts of online explanations to the assigned homework.…”
Section: Introductionmentioning
confidence: 99%